(untitled) (Innovative professional education, 2023)
The project culture of vocational teachers is characterized by ambiguity and manifests itself in different contexts. Its development is based on the use of a set of provisions and principles of the following methodological approaches: systemic, synergistic, integrative, competence-based, activity-based, subject-subject, acmeological, cultural, andragogical, professionalographic, technological. The significance and feasibility of methodological approaches in solving problems of developing the project culture of vocational teachers are specified.